Application of biochar derived from used cigarette filters in direct carbon solid oxide fuel cell. (29th June 2022) - Tong, Xin; Hou, Junwei; Li, Yuzhi; Li, Hualing; Wu, Weichuang; Guo, Yanning; Liu, Yiying; Fu, Daishuang; Huang, Xingkai; Xiong, Zhe; Jiang, Jun; Qi, Long; et al.
Abstract: As a typical waste, used cigarette filters (UCFs) are difficult to biodegrade and harmful to the environment. The direct carbon solid oxide fuel cell (DC-SOFC) is an energy conversion device that can utilize carbon directly, including biochar, as fuel. We report a superior DC-SOFC powered by Fe-loaded UCF biochar in this paper. The microstructure and composition are characterized, indicating that the UCF biochar is micron-sized and contains metal elements such as K and Ca that are beneficial to the performance of DC-SOFC. The peak power density of the cell fueled by pure UCF biochar is 308 mW cm −2 and increases to 341 mW cm −2 after loading Fe as the catalyst, which is comparable to that of the cell with Fe-loaded activated carbon (368 mW cm −2 ). It proves the feasibility of the UCF biochar as fuel for DC-SOFCs, providing a theoretical basis and technical demonstration for the disposal and transformation of solid waste. Highlights: A biochar derived from the used cigarette filters is applied as fuel in DC-SOFCs. DC-SOFC output increases from 308 to 341 mW cm −2 at 850 °C by Fe catalyst. Accumulated elements in used cigarette filters char acts as catalyst for Boudouard reaction. Fe-loaded UCF biochar is a promising fuel for DC-SOFC.